HUMAN GENETIC VARIANTS AND THEIR ANALYSIS: CURRENT STATE AND FUTURE PERSPECTIVES - Lara Slavec; Ksenija Geršak; Nataša Karas Kuželički; Katarina Trebušak Podkrajšek (The Society for Children with Metabolic Disorders, 2020)
Human genetic variants occur throughout the whole genome, both in the coding and non-coding regions. In addition to defining genetic diversity among individuals, they may, in some instances, cause various genetic diseases, many of which have their onset in childhood. In the first part of the review article, we describe different types of genetic variants, ranging from minor sequence changes to major chromosomal aberrations. This is followed by a presentation of some of the most important approaches (cytogenetic and molecular genetic) that are used to detect genetic variants in clinical practice. We put greater emphasis on sequencing methods, as they allowed us to gain insight into the nucleotide sequence of the entire genome, and therefore revolutionised the field of molecular genetic diagnostics. We also highlight the problems that arise in determining genetic variants through next-generation sequencing (NGS) methods and outline the benefits of the latest sequencing techniques − long-read sequencing. Today, a substantial proportion of human genetic variants associated with the development of genetic diseases, are still unknown. Therefore, we conclude the article by presenting some possible approaches that could improve the detection of genetic variants at the individual level.